Subcellular localization of Rap1 GTPase activator CalDAG‐GEFI is orchestrated by interaction of its atypical C1 domain with membrane phosphoinositides. (30th December 2019) - Sarker, Muzaddid; Goliaei, Ardeshir; Golesi, Florence; Poggi, Marjorie; Cook, Aaron A.; Khan, Mohammad A. I.; Temple, Brenda R.; Stefanini, Lucia; Canault, Matthias; Bergmeier, Wolfgang; Campbell, Sharon L.
Abstract: Background: The small GTPase Rap1 and its guanine nucleotide exchange factor, CalDAG‐GEFI (CDGI), are critical for platelet function and hemostatic plug formation. CDGI function is regulated by a calcium binding EF hand regulatory domain and an atypical C1 domain with unknown function. Objective: Here, we investigated whether the C1 domain controls CDGI subcellular localization, both in vitro and in vivo. Methods: CDGI interaction with phosphoinositides was studied by lipid co‐sedimentation assays and molecular dynamics simulations. Cellular localization of CDGI was studied in heterologous cells by immunofluorescence and subcellular fractionation assays. Results: Lipid co‐sedimentation studies demonstrated that the CDGI C1 domain associates with membranes through exclusive recognition of phosphoinositides, phosphatidylinositol (4, 5)‐biphosphate (PIP2) and phosphatidylinositol (3, 4, 5)‐triphosphate (PIP3). Molecular dynamics simulations identified a phospholipid recognition motif consisting of residues exclusive to the CDGI C1 domain. Mutation of those residues abolished co‐sedimentation of the C1 domain with lipid vesicles and impaired membrane localization of CDGI in heterologous cells. Conclusion: Our studies identify a novel interaction between an atypical C1 domain and phosphatidylinositol (4, 5)‐biphosphate and phosphatidylinositol (3, 4, 5)‐triphosphate in cellular membranes, which is critical for Rap1 signaling in health and disease.